Influence of precursor porosity on sodium and sulfur promoted iron/carbon Fischer-Tropsch catalysts derived from metal-organic frameworks - Oschatz, Martin; Krause, Simon; Krans, N. A.; Mejia, C. Hernandez; Kaskel, Stefan; De Jong, K. P. (Chemical Communications, 2017)
Iron-based metal-organic frameworks (MOFs) with varying porosity are converted by pyrolysis into iron/carbon catalysts with predetermined composition and tailored pore structural features for the Fischer-Tropsch synthesis of lower C2-C4 olefins. Significantly higher activity arises for catalysts with higher porosity and decreased iron particle size derived from hierarchical MOF xerogel/aerogel precursors as compared to a purely microporous MOF. Post-synthetic functionalization using sodium and sulfur promoters further enhances the catalytic properties.
CRIS-Team Scopus Importer:2022-04-14